2012
DOI: 10.1016/j.molcel.2011.10.018
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Signaling Triggers Degradation of Histone Methyltransferases through APC/CCdh1 in Senescent Cells

Abstract: Both the DNA damage response (DDR) and epigenetic mechanisms play key roles in the implementation of senescent phenotypes, but very little is known about how these two mechanisms are integrated to establish senescence-associated gene expression. Here we show that, in senescent cells, the DDR induces proteasomal degradation of G9a and GLP, major histone H3K9 mono- and dimethyltransferases, through Cdc14B- and p21(Waf1/Cip1)-dependent activation of APC/C(Cdh1) ubiquitin ligase, thereby causing a global decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
166
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(170 citation statements)
references
References 29 publications
0
166
1
3
Order By: Relevance
“…However, because the chromatin adjacent to the damaged DNA needs to be open in order to increase the accessibility of repair proteins, H3K9 methylation has to be reversed to promote the repair process. It has been demonstrated that DNA damage induces the degradation of G9a/GLP, which results in decreased H3K9me2 at the promoters of IL-6 and IL-8 in senescent cells (Takahashi et al, 2012). In addition, H3K9me2/3 demethylases KDM4B and KDM4D are recruited to the DNA damage sites mediated by PARP1, and are responsible for H3K9 demethylation (Khoury-Haddad et al, 2014;Young et al, 2013).…”
Section: Methylationmentioning
confidence: 99%
“…However, because the chromatin adjacent to the damaged DNA needs to be open in order to increase the accessibility of repair proteins, H3K9 methylation has to be reversed to promote the repair process. It has been demonstrated that DNA damage induces the degradation of G9a/GLP, which results in decreased H3K9me2 at the promoters of IL-6 and IL-8 in senescent cells (Takahashi et al, 2012). In addition, H3K9me2/3 demethylases KDM4B and KDM4D are recruited to the DNA damage sites mediated by PARP1, and are responsible for H3K9 demethylation (Khoury-Haddad et al, 2014;Young et al, 2013).…”
Section: Methylationmentioning
confidence: 99%
“…10) or the senescence messaging secretome (SMS; ref. 5), hereafter referred to as SASP, is induced by DDRs (11,12) and contributes positively or negatively to cancer development, depending on the biologic context (13)(14)(15). Because some of the SASP factors, such as interleukin (IL)-6 and plasminogen activator inhibitor-1, are reportedly associated with increased cancer risk in obesity (1, 16), we explored the possibility that SASP may contribute positively to obesityassociated cancer development using the obese mouse as a model system.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a scenario, where the discussed proteins come together and may become involved in each other's regulation. 66,67 The induction and maintenance of pluripotency has traditionally been interpreted to depend on the expression of core pluripotency factors. A more recent, not necessarily contradictory concept interprets pluripotency as an intricate balance between the activities of lineage specifying factors, which on their own would promote a specific developmental direction.…”
Section: Mad2l2mentioning
confidence: 99%